Trait and State Approaches to Explaining Argument Structures. - Suzuki, Shinobu (Communication Quarterly)
This study examines how an individual's argumentative communication traits and involvement, a situational factor, account for the way the individual structures his or her written argument. Research questions were posited to ask which of the 3 models — the Interaction Model, the Mediation Model, and the Simple Main Effects Model — best predicts the use of macro- and micro-structures of written argument. Logistic and multiple regression analyses were conducted to analyze 229 usable responses collected from Japanese college students. The results revealed that the Mediation Model and the Simple Main Effects Model are viable models. Argumentative traits and involvement interrelate to explain argument structures, revealing a somewhat complex but interpretable mechanism. Reprinted by permission of the publisher.